2010
DOI: 10.1039/b927582g
|View full text |Cite
|
Sign up to set email alerts
|

New reaction of β-diketiminatoeuropium complex: sterically induced oxidation–coupling of β-diketiminato ligands

Abstract: Attempted synthesis of sterically demanding tris-beta-diketiminate complexes of europium led to oxidation-coupling of beta-diketiminates and the formation of the THF-solvated divalent europium complex Eu(L(2,6-Me(2)))(2)(THF) (L(2,6-Me(2)) = [{N(2,6-Me(2)C(6)H(3))C(Me)}(2)CH](-)), while the normal tris-beta-diketiminate complex Eu(L(2-Me))(3) for the less bulky ligand L(2-Me) ([{N(2-MeC(6)H(4))C(Me)}(2)CH](-)) was isolated by the same procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 19 publications
4
33
1
Order By: Relevance
“…If one takes into account this non-bonding AleAl interaction then each aluminum center is six coordinate with distorted geometrical parameters. The Al1eO1 distance is shorter than is observed in 2, (1.7524(9) Å cf 1.7795 (14) but the Al1eN1 bond is slightly longer, 2.0334(10) Å compared to 2.0062 (17). The Al1-N1A bond length of 1.93241(10) Å is significantly shorter than the AleN interactions observed in 2, and is indicative of a covalent AleN interaction.…”
Section: Resultscontrasting
confidence: 49%
See 1 more Smart Citation
“…If one takes into account this non-bonding AleAl interaction then each aluminum center is six coordinate with distorted geometrical parameters. The Al1eO1 distance is shorter than is observed in 2, (1.7524(9) Å cf 1.7795 (14) but the Al1eN1 bond is slightly longer, 2.0334(10) Å compared to 2.0062 (17). The Al1-N1A bond length of 1.93241(10) Å is significantly shorter than the AleN interactions observed in 2, and is indicative of a covalent AleN interaction.…”
Section: Resultscontrasting
confidence: 49%
“…For example, reaction of a b-diketiminate ligand with AgPF 6 saw a one electron oxidation of the ligand by Ag(I), affording a radical species that subsequently undergoes radical coupling to form a neutral dimeric ligand [16]. Similarly, the reaction of [Na{N(2,6-Me 2 C 6 H 3 )C(Me)} 2 CH] with EuCl 3 saw the isolation of a dimeric coupled organic product, [{N(2,6-Me 2 C 6 H 3 ) C(Me)} 2 CH] 2 [17]. Nevertheless, although ligand coupling is less common for main group metals it is not unprecedented; the reaction of 'GaI' with ArN]C(H)Py (Ar ¼ C 6 H 3 Pr i 2 -2,6 or Bu t ) gives a reductively coupled diamido-digallium(iii)complex,…”
Section: Resultsmentioning
confidence: 98%
“…Interestingly, BDI oxidative coupling is avoided when the ligand carbon framework does not carry alkyl substituents, allowing isolation of dinuclear Ag(I) complex [Ag 2 (BDI Dipp,H ) 2 ] (Scheme 17bottom). 88,89 The authors propose that the reaction proceeds through a sterically-induced reduction pathway to explain such ligand dependency. 84 Early attempts to prepare (BDI*)TiCl 3 from the salt-metathesis reaction between TiCl 4 and Li(BDI*) proved unsuccessful with the oxidative C-C coupling product being the sole reaction product isolated.…”
Section: Oxidative Couplingmentioning
confidence: 99%
“…[1] These ligands have also been proven under certain conditions to undergo transformations that include reduction to di-or trianionic species by a reducing agent, [2] deprotonation to a dianion by means of an alkane elimination [3a-e] or a β-diketiminate elimination, [3f] and oxidation coupling to a neutral molecule. [4] Recently we have reported that the β-diketiminate group in a sterically demanding complex, such as tris(β-diketiminato)lanthanide complex, can also serve as an active species in homogeneous catalysis, and the activity was found to depend both on the size of the β-diketiminato ligands and the central metals.…”
Section: Introductionmentioning
confidence: 99%